Neuropathic Corneal Pain after Coronavirus Disease 2019 (COVID-19) Infection - Natalie Shi Qi Wong; Chang Liu; Molly Tzu-Yu Lin; Isabelle Xin Yu Lee; Louis Tong; Yu-Chi Liu (Diseases, 2024)
Introduction: This is a case report of a patient with neuropathic corneal pain after coronavirus disease 2019 (COVID-19) infection. Methods: A previously healthy 27-year-old female presented with bilateral eye pain accompanied by increased light sensitivity 5 months after COVID-19 infection. She was diagnosed with neuropathic corneal pain based on clear corneas without fluorescein staining, alongside the presence of microneuromas, dendritic cells, and activated stromal keratocytes identified bilaterally on in vivo confocal microscopy. Results: The patient’s tear nerve growth factor, substance P, and calcitonin gene-related peptide levels were 5.9 pg/mL, 2978.7 pg/mL, and 1.1 ng/mL, respectively, for the right eye and 23.1 pg/mL, 4798.7 pg/mL, and 1.2 ng/mL, respectively, for the left eye, suggesting corneal neuroinflammatory status. After 6 weeks of topical 0.1% flurometholone treatment, decreased microneuroma size, less extensive dendritic cells, and reduced tear nerve growth factor and substance P levels were observed. The scores on the Ocular Pain Assessment Survey showed an improvement in burning sensation and light sensitivity, decreasing from 80% and 70% to 50% for both. Conclusions: Neuropathic corneal pain is a potential post-COVID-19 complication that warrants ophthalmologists’ and neurologists’ attention.